Performance pay, sorting, and outsourcing - Fred Henneberger; Alfonso Sousa-Poza; Alexandre Ziegler (Institute for the Study of Labor (IZA), 2007)
Implementing performance pay requires that workers' output be measured. When measurement costs differ among firms, those with a measurement cost advantage choose to implement performance pay. They attract the best workers, and both the level and variability of compensation are higher at these firms than at salary firms. Workers may select firms with different compensation methods at different stages of their work life. Productive workers start at performance pay firms and switch to salary firms once their productivity is revealed. The magnitude of the resulting worker flows depends on the payoff from effort and is therefore related to the age profile of the wage differential between performance pay and salary firms. Advantages in measuring worker productivity constitute a plausible explanation for the emergence of specialized business related service (BRS) firms. Accordingly, BRS firms should make a much wider use of performance pay and employ better workers than diversified corporations. Data from the 1998 Swiss Wage Structure Survey confirm the model's predictions both for the economy at large and for BRS firms.
Keywords: 330; Asymmetric information; sorting; incentives; productivity; outsourcing; Leistungsorientierte Vergütung; Personalbeurteilung; Kosten; Arbeitsproduktivität; Messung; Asymmetrische Information; Arbeitsmobilität; Unternehmensdienstleistung; Outsourcing; Theorie; Schweiz